2015
DOI: 10.1016/j.cois.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of physiological processes by microRNAs in insects

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that function in gene regulatory processes in plants and animals by targeting sites within messenger RNA. In insects, miRNAs have been shown to regulate a variety of physiological processes throughout insect development, including molting, metamorphosis, oogenesis, embryogenesis, behavior and host-pathogen interactions. The roles of miRNAs in the model organism, Drosophila melanogaster, have been studied extensively due to the conserved nature of miRNA function amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…An important innovation that explains most of the insect evolutionary success has been the holometabolan metamorphosis, by which the juvenile stages can adopt a body plan very different from that of the adult, thus allowing the exploitation of new resources8. Recent reviews emphasize the importance that miRNAs play in insects910, also in metamorphosis11.…”
mentioning
confidence: 99%
“…An important innovation that explains most of the insect evolutionary success has been the holometabolan metamorphosis, by which the juvenile stages can adopt a body plan very different from that of the adult, thus allowing the exploitation of new resources8. Recent reviews emphasize the importance that miRNAs play in insects910, also in metamorphosis11.…”
mentioning
confidence: 99%
“…In diverse cellular programs, miRNA plays a key role and involves in cell growth, differentiation, apoptosis, and many other physiological processes , Park et al 2015. In insects, the studies on miRNAs are mostly focused on the development, behavior, and hostpathogen interactions (Lucas et al 2015). Recent evidence has shown that a few miRNAs participate in the regulation of insecticide resistance in mosquitoes, but the exact role of miRNA in pyrethroid resistance is still under little attention yet .…”
mentioning
confidence: 99%
“…Hence, miRNAs play significant roles in governing multiple functions in animals and plants via integrating sophisticated miRNA-mRNA regulatory networks (10,11). In the mosquito, previous studies have shown that several miRNAs manipulate host-pathogen interactions, contributing to maintenance of endosymbiont Wolbachia infection or resistance to DENV (dengue virus) infection (12)(13)(14).…”
mentioning
confidence: 99%